Repository of Instructional and Assessment Techniques for OBE-Based Instructional Module Development System - Bansal, Srividya K.; Dalrymple, Odesma (Journal of Engineering Education Transformations, 2016)
Instructional Module Development System (IMODS) project IMODS) project aims to assist educators in developing a STEM-based curriculum, even if the educator has not had extensive or formal training in educational methods. Research shows that choice of appropriate curriculum and assessment methods are critical in successfully teaching students and having the students retain the information taught. The IMODS strives to be a tool to assist educators in building that curriculum which will include an instructional and assessment plan. To successfully achieve this goal, a variety of educational, instructional, and assessment strategies are required to be integrated into the program. In this paper, we present the design and implementation of a repository of current best pedagogical and assessment practices that will be part of IMODS. We also present integration of this repository into the IMODS software to present options for assessment and instruction that align with the type/level of student learning desired based on selections the user makes when defining the learning objectives of the course.